Examination of Deflection and Cracking in Classroom 1A's Concrete Structures: a Case Study and Retrofit Approaches - Aco Wahyudi Efendi (Teknik Sipil, Politeknik Negeri Ketapangg, 2026)
Providing an emphasis on the second-floor slab and beams, this study provides a thorough investigation of the bending and cracking seen in the concrete structures of Classroom 1A at SDIT Auliya Balikpapan. In multi-story buildings, excessive deflection and critical fracture widths can seriously jeopardize serviceability, user comfort, and structural integrity [1], [2]. The present state of the structure was evaluated in detail utilizing a combination of Finite Element Method (FEM) analysis using LISA FEA and Non-Destructive Testing (NDT) techniques, such as Ultrasonic Pulse Velocity (UPV), Crack Width Test, Rebar Scanner Test, and Schmidt Hammer Test. The results showed that although the majority of the beams had acceptable crack widths and deflection, the second-floor slab had a considerable 30 mm deflection, which was more than the 19.44 mm allowed by SNI 2847:2019 [3], [4] , and some of the beams (R1.B1, R1.B2, and R2.B4) also had crack widths that were greater than the 0.41 mm threshold [5], [6]. Additionally, FEM analysis revealed stress concentrations in the slab that exceeded the nominal compressive strength of the concrete. In order to restore the classroom building's structural safety and long-term durability, a retrofitting solution utilizing Fiber Reinforced Polymer (FRP) is suggested, along with ongoing monitoring and possible reevaluation of design criteria.